Assembly of Homochiral Magneto-Optical Dy6 Triangular Clusters by Fixing Carbon Dioxide in the Air - Liu, Cai-Ming; Hao, Xiang; Li, Xi-Li (Molecules (Basel, Switzerland), 2024)
A new hydrazone Schiff base bridging ligand (H2LSchiff (E)-N′-((1-hydroxynaphthalen-2-yl)methylene)pyrazine-2-carbohydrazide) and L/D-proline were used to construct a pair of homochiral Dy6 cluster complexes, [Dy6(CO3)(L-Pro)6(LSchiff)4(HLSchiff)2]·5DMA·2H2O (L-1, L-HPro = L-proline; DMA = N,N-dimethylacetamide) and [Dy6(CO3)(D-Pro)6(LSchiff)4(HLSchiff)2]·5DMA·2H2O (D-1, D-HPro = D-proline), which show a novel triangular Dy6 topology. Notably, the fixation of CO2 in the air formed a carbonato central bridge, playing a key role in assembling L-1/D-1. Magnetic measurements revealed that L-1/D-1 displays intramolecular ferromagnetic coupling and magnetic relaxation behaviours. Furthermore, L-1/D-1 shows a distinct magneto-optical Faraday effect and has a second harmonic generation (SHG) response (1.0 × KDP) at room temperature. The results show that the immobilization of CO2 provides a novel pathway for homochiral multifunctional 4f cluster complexes.